Experimental investigation of the mechanism of salt precipitation in the fracture during CO2 geological sequestration. (July 2022) - He, Di; Xu, Ruina; Ji, Tiancheng; Jiang, Peixue
Highlights: Design a micromodel to simulate reservoir fracture to study the mechanism and law of salt precipitation in fracture during CO2 geological storage. Under hydrophilic conditions, reducing the CO2 injection rate and increasing the solution concentration will increase the amount of salt precipitation in the fracture and impair reservoir injectivity. Increasing the contact angle of the rock will greatly reduce the amount of salt precipitation in the fracture, which is less effect on reservoir injectivity. Similar conclusions can also be applied to caprock fractures, and the occurrence of salt precipitation in caprock fractures will have the effect of self-healing of the fractures. Abstract: Injectivity is an important indicator when it comes to evaluating the geological storage of CO2 . It is commonly accepted that salt precipitation damages the injectivity during the CO2 injection process. Numerous studies have been conducted on the salt precipitation mechanism in homogeneous reservoirs. However, the mechanism of salt precipitation in fractures during CO2 injection and its influence on the injectivity need to be studied in depth. Therefore, in this study, a micromodel that simulates a reservoir fracture was designed and pore-scale experiments were conducted to study the effects of the CO2 injection rate, the concentration of the solution, and the rock's wettability on the salt precipitation in the fracture. It was found that under hydrophilic conditions, reducing the CO2 injection rate and increasing the concentration of the solution increased the amount of salt precipitation in the fracture and impaired the micromodel's injectivity. In contrast, increasing the CO2 injection rate and the contact angle of the rock greatly reduced the amount of salt precipitation in the fracture, which had a less adverse effect on the micromodel's injectivity.